ACC synthase and its cognate E3 ligase are inversely regulated by light - Yoon, Gyeong Mee (Landes Bioscience, 2013)
1-aminocyclopropane-1-carboxylic acid (ACC) synthase (ACS) is the key enzyme in ethylene biosynthesis, catalyzing the conversion of S-adenosylmethionine (AdoMet) to ACC, which is the immediate precursor of ethylene. The regulation of ACS protein stability plays an important role in controlling ethylene biosynthesis. We have recently shown that 14-3-3 positively regulates ACS protein stability by both a direct effect and via downregulation of the stability of the E3 ligases regulating its turnover, Ethylene Overproducer1 (ETO1)/ETO1-like (EOL). Here, we report that treatment of etiolated Arabidopsis seedlings with light rapidly increases the stability of ACS5 protein. In contrast, light destabilizes the ETO1/EOLs proteins, suggesting that light acts to increase ethylene biosynthesis in part through a decrease in the level of the ETO1/EOL proteins. This demonstrates that the ETO1/EOLs are regulated in response to at least one environmental cue and that their regulated degradation may represent a novel input controlling ethylene biosynthesis.